Analisis Pemanis Sintesis Natrium Sakarin Dan Natrium Siklamat Dalam Teh Kemasan - Roslinda Rasyid; Melly Yohana; Mahyuddin Mahyuddin (STIFARM Padang, 2011)
It has been studied analysis of the synthetic sweetener sodium saccharin and sodium cyclamate in the tea drink. Synthetic sweetener were identified by color reactions and microcrystalline test. The result were compared with standard substances. Of the four samples examined here are three samples contain sodium cyclamate, while one other sample not find the content of sodium cyclamate and sodium saccharin. Levels of sodium cyclamate in the sample were determined by uv-vis spektofotometer.These levels are below the limit determined by Health Minister’s Regulation of Indonesian Republic which is 0.3 % for the soft drink.